Association between the TyGBS index and all-cause and cardiovascular mortality in diabetic stroke patients - Lu, Gaggui; Miao, Xingyu; Meng, Facai; Liu, Kaifei; Yang, Xiaomei; Zhang, Man (Frontiers in Endocrinology, 2025)
BackgroundStroke patients with diabetes face elevated mortality risks, posing a global public health challenge. The TyG (Triglyceride-Glucose) index and Oxidative Balance Score (OBS) are potential predictors of mortality, but their combined impact remains unclear. This study explores the association between Triglyceride-Glucose to Oxidative Balance Score Ratio (TyGBS) and all-cause and cardiovascular mortality in diabetic stroke patients.MethodsData from 556 diabetic stroke patients in the NHANES 1999–2018 cohort were analyzed. Mortality outcomes were determined using the National Death Index. TyGBS, calculated as the TyG index divided by OBS, was assessed for its association with mortality through Kaplan-Meier analysis, multivariable Cox regression, restricted cubic splines (RCS), and subgroup analyses.ResultsOver a mean follow-up of 73 months, 210 (49.4%) patients died, including 65 (15.3%) from cardiovascular causes. Higher TyGBS levels were significantly associated with increased mortality risks. Kaplan-Meier analysis showed the lowest mortality in the lowest TyGBS quartile (Q1) and the highest in Q4 (log-rank p<0.001). Cox regression revealed that each unit increase in TyGBS raised all-cause mortality risk by 360% (HR 4.60, 95% CI 3.21–6.59) and cardiovascular mortality risk by 357% (HR 4.57, 95% CI 2.43–8.60). The RCS analysis indicated a nonlinear association, showing a significant increase in mortality risk when TyGBS was less than 1.163 (p for nonlinearity = 0.002).ConclusionTyGBS, a novel ratio integrating metabolic and oxidative pathways, demonstrates a critical clinical threshold for prioritizing interventions in diabetic stroke.